Nyakaza-Move-for-Health: A Culturally Tailored Physical Activity Intervention for Adolescents in South Africa Using the Intervention Mapping Protocol - Patrick M. Zimu; Hendrik J. Van Heerden; Jeanne M. Grace (SAGE Publishing, 2024)
Background: The Nyakaza-Move-for-Health intervention program was developed in response to the alarming rise in non-communicable diseases (NCDs) globally, in sub-Saharan Africa and South Africa. The rise in NCDs is attributed to the low levels of participation in physical activity (PA) among adolescents. Therefore, this study aimed to design a culturally tailored PA intervention for adolescents, guided by the Intervention Mapping (IM) protocol. The intervention program aims to address the multifaceted determinants of physical activity behavior, promote healthy lifestyles and improve adolescent fitness levels. Methods: The Intervention Mapping protocol was applied to design the intervention program. The IM has 6 steps: (1) Needs assessment, (2) developing a logic model of the problem (LMP), (3) Formulating program outcomes and objectives, (4) Program design and production, (5) Generating implementation plan, and (6) Generating intervention evaluation plan. Participants included (n = 48) adolescent learners recruited from 8 (n = 8) participating schools. Adolescent learners participated in focus group discussions (FGD) to identify personal, interpersonal and environmental determinants of physical inactivity. Twenty-six (n = 26) key informant stakeholders participated in a stakeholder engagement workshop (SEW) to determine the motivators and constraints in implementing physical activity interventions. Results: The Nyakaza intervention program's process development involved extensive stakeholder engagement, capacity development training, and integration of community feedback into the design. The intervention included a social marketing campaign and structured after-school physical activity sessions based on the Health Belief Model (HBM) and Transtheoretical Model (TTM). Implementation and evaluation plans were created, emphasizing real-time monitoring and adaptations. Strategies to enhance parental and community support were developed to address participation barriers. Although not tested in this study, these plans laid a robust foundation for fostering sustainable behavior change and improving physical activity among adolescents in resource-constrained settings. Conclusion: The Nyakaza-Move-for-Health intervention demonstrates a promising framework for promoting adolescent physical activity and addressing Non-Communicable Diseases in a culturally relevant manner. The systematic approach, grounded in the intervention mapping protocol, ensured a robust and replicable intervention design. Future research should focus on long-term follow-up, integrating objective physical activity measures, and expanding the program to include nutrition education. Addressing identified barriers, such as parental involvement, is crucial for enhancing the intervention's effectiveness and sustainability.